Cyclobotryoxide, a phytotoxic metabolite produced by the plurivorous pathogen Neofusicoccum australe. - Andolfi, Anna; Maddau, Lucia; Cimmino, Alessio; Linaldeddu, Benedetto T.; Franceschini, Antonio; Serra, Salvatorica; Basso, Sara; Melck, Dominique; Evidente, Antonio (Journal of natural products, 2012)
Two isolates of Neofusicoccum australe belonging to ITS haplotypes H4 and H1 and associated with grapevine cordon dieback and branch dieback of Phoenicean juniper, respectively, have been shown to produce in vitro structurally different secondary metabolites. From the strain BOT48 of N. australe (haplotype H4) a new cyclohexenone oxide, namely, cyclobotryoxide, was isolated together with 3-methylcatechol and tyrosol. Cyclobotryoxide was characterized as (1S,5R,6S)-5-hydroxy-3-methoxy-4-methyl-7-oxabicyclo[4.1.0]hept-3-en-2-one by spectroscopic, optical, and chemical methods. The strain BL24 (haplotype H1) produced tyrosol along with botryosphaerone D and (3S,4S)-3,4,8-trihydroxy-6-methoxy-3,4-dihydro-1(2H)-naphthalenone. The metabolites obtained from both strains were tested at four concentrations on leaves of grapevine cv. Cannonau, holm oak, and cork oak by the leaf puncture assay. Cyclobotryoxide proved to be the most phytotoxic compound. Tyrosol and cyclobotryoxide were also tested on detached grapevine leaves at concentrations of 0.25 and 0.5 mg/mL. Only cyclobotryoxide was found to be active in this bioassay.
The following values have no corresponding Zotero field: accession-num: 23046443
Keywords: Ascomycota; Ascomycota: chemistry; Bicyclo Compounds, Heterocyclic; Bicyclo Compounds, Heterocyclic: chemistry; Bicyclo Compounds, Heterocyclic: isolation & purif; Bicyclo Compounds, Heterocyclic: pharmacology; Catechols; Cyclohexanones; Cyclohexanones: chemistry; Cyclohexanones: isolation & purification; Cyclohexanones: pharmacology; Juniperus; Juniperus: microbiology; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Mycotoxins: isolation & purification; Mycotoxins: pharmacology; Nuclear Magnetic Resonance, Biomolecular; Quercus; Quercus: drug effects; Stereoisomerism; Vitis; Vitis: drug effects

Implementation of a module for risk of ozone impacts assessment to vegetation in the Integrated Assessment Modelling system for the Iberian Peninsula. Evaluation for wheat and Holm oak. - de Andrés, Juan Manuel; Borge, Rafael; de la Paz, David; Lumbreras, Julio; Rodríguez, Encarnación (Environmental pollution (Barking, Essex : 1987), 2012)
A module to estimate risks of ozone damage to vegetation has been implemented in the Integrated Assessment Modelling system for the Iberian Peninsula. It was applied to compute three different indexes for wheat and Holm oak; daylight AOT40 (cumulative ozone concentration over 40 ppb), cumulative ozone exposure index according to the Directive 2008/50/EC (AOT40-D) and POD(Y) (Phytotoxic Ozone Dose over a given threshold of Y nmol m(-2) s(-1)). The use of these indexes led to remarkable differences in spatial patterns of relative ozone risks on vegetation. Ozone critical levels were exceeded in most of the modelling domain and soil moisture content was found to have a significant impact on the results. According to the outputs of the model, daylight AOT40 constitutes a more conservative index than the AOT40-D. Additionally, flux-based estimations indicate high risk areas in Portugal for both wheat and Holm oak that are not identified by AOT-based methods.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 22398018
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: toxicity; Chemical; CMAQ WRF; Critical level; Environmental Monitoring; Environmental Monitoring: methods; iberian peninsula; Models; Ozone; Ozone risk assessment; Ozone: analysis; Ozone: toxicity; Portugal; Quercus; Quercus: drug effects; Quercus: growth & development; Risk Assessment; Stomatal conductance; Triticum; Triticum: drug effects; Triticum: growth & development

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M; Humara, Jaime M; Revilla, Angeles; Ordás, Ricardo J (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M.; Humara, Jaime M.; Revilla, Angeles; Ordás, Ricardo J. (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
The following values have no corresponding Zotero field: accession-num: 19543858
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology